Inherent Safety Intervention Framework - Chan , Tuck Leong (2008)
Despite being an attractive proposition in terms of safety and cost performance, the actual implementation of Inherent Safety in design is not widely observed in the industries. This has been documented in publications which indicated the lack of an effective Inherent Safety Quantification methodology and the lack of integration between process design stages with risk and consequence estimation are hurdles to designing inherently safer process plants. Initial attempts by other researches to quantify level of inherent safety resulted in the invention of few indices which are based on reactions involved and have been able to differentiate the level of inherent safety for various routes producing the same product. These indices account for temperature, pressure and presences of the chemicals in the reactions individually. These indices are not able to reflect the interaction of these process parameters and the actual composition of the process streams and their impact on level of inherent safety. This research developed a methodology which is able to differentiate level of inherent safety for various process routes and subsequently of the various process streams within a process route. The new indices known as Process Route Index (PRI) and Process Stream Index (PSI) are based on interactions of various process parameters and actual composition of process streams. These indices are part of the Inherent Safety Intervention Framework (ISIF) which is proposed and proven in this research to allow for proactive identification of consequences of a hazard and subsequently allow modifications based on Inherent Safety principles. Owing to its integration with process simulator, the ISIF can quickly reflect the changes of inherent safety levels when process modifications are simulated iteratively. In order to represent risk in a format familiar to many, this research proposed the concept of Inherent Risk Assessment (IRA) which is similar to Quantitative Risk Assessment (QRA) which is widely used. Similar to QRA, the IRA represent risk by means of a FN Curve. IRA reflects the inherent risk within the process being designed without yet considering mechanism and procedures to reduce risk to an ALARP level as the design stages progresses along. It is proposed that the IRA be used to determine initial acceptance, by government agencies, of a process being designed based on predetennined set of assumptions. The case studies presented towards the end of this research clearly demonstrated the effectiveness of the ISIF to quantify level of inherent safety at process route selection level using PRJ and using the PSI to prioritize streams for modification purposes. Based on the PRJ, an inherently safer route can be chosen and modification based on the principles of inherent safety can be implemented at the streams scoring higher PSI numbers. The IRA complements the work by representing the level of risk inherent to the process being considered in comparison to the limits set by local authorities.